Unfulfilled potential Irrigation and small farmers- 2 case studies from Tanzania - Mdee, Anna (2016)
Presented by Dr. Anna Mdee, Mzumbe University/University of Sussex at the workshop on “New Directions for Irrigation Development in Tanzania: The Context of Public Private Partnership”, September 2, 2016.